Cross-sectional survey of child weight management service provision by acute NHS trusts across England in 2020/2021. Issue 11 (10th November 2022) - Mears, Ruth; Leadbetter, Sofia; Candler, Toby; Sutton, Hannah; Sharp, Deborah; Shield, Julian P H
Abstract : Objective: With one in five children in England living with obesity, we mapped the geographical distribution and format of child weight management services provided by acute National Health Service (NHS) trusts across England, to identify breadth of service provision. Design: A cross-sectional survey. Setting: The survey was sent to acute NHS trusts (n=148) in England in 2020, via a freedom of information request. Participants: Responses were received from 139 of 148 (94%) acute NHS trusts, between March 2020 to March 2021. Outcome measures: The survey asked each acute NHS trust whether they provide a weight management service for children living with obesity. For those trusts providing a service, data were collected on eligibility criteria, funding source, personnel involved, number of new patients seen per year, intervention duration, follow-up length and outcome measures. Service characteristics were reported using descriptive statistics. Service provision was analysed in the context of ethnicity and Index of Multiple Deprivation score of the trust catchment area. Results: From the 139 survey respondents, 23% stated that they provided a weight management service for children living with obesity. There were inequalities in the proportion of acute NHS trusts providing a service across the different regions of England, ranging from 4% (Midlands) to 36% (London). For trusts providing a service, there was variability in the number of new cases seen per year, eligibility criteria, funding source, intervention format and outcome measures collected. A multidisciplinary approach was not routinely provided, with only 41% of services reporting ≥3 different staff disciplines. Conclusion: In 2020/2021, there were geographical inequalities in weight management service provision by acute NHS trusts for children living with obesity. Services provided lacked standardisation, did not routinely offer children multidisciplinary care and were insufficient in size to meet need.